Polymer additive for directing homogeneous zinc deposition and its preparation method and application

The prepared copolymer additive forms a uniform protective layer in the zinc ion battery, solves the problems of zinc dendrite growth and side reactions, improves the stability and performance of the zinc ion battery, and is suitable for efficient and low-cost improvement of aqueous zinc ion batteries.

CN118812793BActive Publication Date: 2025-10-17SUN YAT SEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410963052.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2025-10-17
Estimated Expiration
2044-07-18

AI Technical Summary

Technical Problem

Aqueous zinc-ion batteries (AZIBs) with zinc metal anodes suffer from problems such as heterogeneous zinc ion deposition/dissolution, hydrogen evolution reaction, and surface byproduct formation, leading to low Coulombic efficiency and zinc dendrite growth, hindering their development.

Method used

A copolymer prepared by free radical copolymerization of isobutylene alcohol polyoxyethylene ether, acrylic acid, sodium styrene sulfonate and hydroxyethyl acrylate is used as a polymer additive in aqueous zinc ion electrolyte to form a uniform and stable protective layer to inhibit side reactions and dendrite growth.

Benefits of technology

It improves the stability and cycle life of zinc-ion batteries, significantly improves the rate performance and cycle stability of zinc-ion batteries, reduces production costs, and has good reversibility and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118812793B_ABST
    Figure CN118812793B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of aqueous zinc ion battery electrolyte additives, and particularly relates to a polymer additive for guiding zinc homogeneous deposition and a preparation method and application thereof. The polymer additive provided by the application is obtained by free radical copolymerization of isobutylene alcohol polyoxyethylene ether, acrylic acid, sodium styrene sulfonate and hydroxyethyl acrylate. The copolymer is used for preparing an aqueous zinc ion electrolyte, and the obtained electrolyte can guide zinc ion homogeneous deposition, obviously inhibit the occurrence of side reactions and the growth of dendrites, and the aqueous zinc ion electrolyte can effectively solve the short circuit and other problems caused by the growth of dendrites in the aqueous zinc ion battery, and can significantly improve the rate performance and cycle stability of the aqueous zinc ion battery. Therefore, the polymer additive provided by the application has great application potential in inhibiting side reactions and optimizing zinc deposition, and is helpful to develop an aqueous zinc ion battery with excellent performance and good energy storage application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of electrolyte additives of aqueous zinc ion batteries, and particularly relates to a polymer additive for guiding zinc homogeneous deposition and a preparation method and application thereof. BACKGROUND

[0002] With the rapid development of global economy and the growth of world population, the limitations of fossil fuels, energy crisis and environmental pollution have become increasingly prominent, posing a severe challenge to the sustainability of development. Therefore, it is urgent to develop and utilize clean, efficient and economic energy resources. With the depletion of fossil fuel resources, renewable energy such as hydroelectricity, solar energy, wind energy, tidal energy, geothermal energy and biomass energy has been widely developed and is regarded as a representative of clean and sustainable energy. However, these energy sources generally face a major challenge - intermittency. In order to overcome this problem, high-efficiency energy storage and conversion devices must be introduced.

[0003] Lithium ion batteries have been widely applied and developed in many fields due to their significant advantages such as high energy density, high rated voltage, low self-discharge rate, light weight and long service life. Although lithium ion batteries currently dominate the new energy storage market, they also have some shortcomings, such as the scarcity of lithium resources, the strictness of manufacturing process, the high cost, the use of active metals and the flammable organic electrolyte. Among them, aqueous zinc ion batteries (AZIBs) using zinc metal as anode are outstanding due to their non-toxicity, high theoretical capacity (820mA·h·g -1 ), excellent safety, stability and compatibility in aqueous solution, and low cost. However, its development still faces challenges, mainly because of the heterogeneous deposition / dissolution of Zn 2+ ions, the inhibition of hydrogen evolution reaction (HER) and the formation of surface by-products, which lead to problems such as low coulombic efficiency (CE), growth of zinc dendrites and surface passivation, thus further hindering the development of AZIBs. From the perspective of practical application, the development of high-efficiency, low-cost and non-toxic additives is considered as a feasible way to improve the above problems. In recent years, polymer additives have attracted much attention due to their high stability and rich functional groups, which can adjust the solvation structure of Zn 2+ ions, improve the ion migration rate. Therefore, the research and development of related new high-performance polymer additives have become the focus of the industry.

[0004] In summary, it is necessary to develop a high-performance polymer additive suitable for AZIBs to improve the problems such as heterogeneous deposition / dissolution of Zn 2+ ions, hydrogen evolution reaction and formation of surface by-products. SUMMARY

[0005] In order to overcome the above-mentioned deficiencies of the prior art, the present application provides a polymer additive which is a copolymer prepared by free radical copolymerization of isobutenyl alcohol polyoxyethylene ether, acrylic acid, sodium styrene sulfonate and hydroxyethyl acrylate. The polymer additive is applied to the preparation of aqueous zinc ion electrolyte, which can effectively guide the homogeneous deposition of zinc ions, reduce the side reactions of the battery during charging and discharging, improve the stability and cycle life of the battery, and is expected to solve the problems of heterogeneous deposition / dissolution of Zn 2+ ions, hydrogen evolution reaction and surface by-products. Moreover, the electrolyte additive has the characteristics of low price, green environmental protection and large-scale production, which has important significance for building high-performance and low-cost aqueous zinc ion batteries.

[0006] In order to achieve the above-mentioned purpose, the technical scheme adopted by the present application is:

[0007] The present application provides a polymer, which is a copolymer of isobutenyl alcohol polyoxyethylene ether, acrylic acid, sodium styrene sulfonate and hydroxyethyl acrylate, and the number average molecular weight of the polymer is 30000-80000, and the molecular structure formula of the polymer is shown as formula I:

[0008]

[0009] The present application provides a preparation method of the polymer of the first aspect, which is obtained by free radical copolymerization of isobutenyl alcohol polyoxyethylene ether, acrylic acid, sodium styrene sulfonate and hydroxyethyl acrylate, and specifically comprises the following steps:

[0010] S1, dissolving acrylic acid, sodium styrene sulfonate, hydroxyethyl acrylate, mercaptopropionic acid and vitamin C in water to prepare a dropping solution;

[0011] S2, dissolving isobutenyl alcohol polyoxyethylene ether and ammonium persulfate in water, heating to 30-35 DEG C, then dropping into the dropping solution of step S1, and controlling the dropping time to be 2.5-3h, controlling the reaction temperature to be 35-45 DEG C during the dropping, continuing to react for 2-3h after the dropping is completed, and obtaining the product after the reaction is completed.

[0012] Preferably, the mass ratio of the isobutenyl alcohol polyoxyethylene ether, acrylic acid, sodium styrene sulfonate, hydroxyethyl acrylate, ammonium persulfate, vitamin C and mercaptopropionic acid is 65-80: 5-10: 5-15: 2.5-10: 1-1.5: 0.1-0.15: 0.5-1.0.

[0013] Preferably, the molecular weight of the isobutenyl alcohol polyoxyethylene ether is 1200-2400, more preferably 2400.

[0014] The third aspect of the present application provides the use of the polymer of the first aspect as an electrolyte additive in a zinc ion battery.

[0015] Preferably, the zinc ion battery is a water-based zinc ion battery.

[0016] The polymer provided by the present application contains a large number of ionic groups (sulfonate and carboxylate groups), ether bonds (polyethylene glycol PEG) and hydroxyl groups, which can interact with water molecules, thereby inhibiting the activity of water molecules, which helps to reduce the side reactions of the battery during charging and discharging, and improves the stability and cycle life of the battery. At the same time, the PEG contained in the polymer has a wetting effect on the zinc metal surface, and the ionic groups contained in the polymer have an anchoring effect on the metal surface, thereby promoting the adsorption of the polymer molecules on the zinc metal surface. This adsorption behavior helps to form a uniform and stable protective layer on the zinc surface, which can prevent side reactions and dendrite growth of zinc metal during battery cycling, thereby improving the safety and electrochemical performance of the battery.

[0017] The fourth aspect of the present application provides a water-based zinc ion battery electrolyte, which comprises the polymer of the first aspect, a zinc salt and water.

[0018] Preferably, the zinc salt is selected from at least one of zinc sulfate, zinc trifluoromethane sulfonate and zinc perchlorate, and more preferably is zinc trifluoromethane sulfonate.

[0019] Preferably, the concentration of the zinc salt is 0.5-3M, and more preferably the concentration is 0.5-2M.

[0020] Preferably, the mass concentration of the polymer in the electrolyte is 1.5%-4.5%, and more preferably is 1.5%, 3.0% and 4.5%, and most preferably is 3.0%. The present application adjusts the adsorption of the polymer additive molecules on the zinc negative electrode surface by adjusting the content of the polymer additive, which not only adjusts the local current density of the electrode tip, but also prevents the free diffusion of zinc ions on the electrode surface. This process promotes the increase of nucleation sites and realizes the homogeneous deposition of zinc. The SEI layer adsorbed on the zinc negative electrode surface can effectively isolate active water molecules, thereby inhibiting the occurrence of side reactions and the growth of dendrites. The adsorption layer on the zinc negative electrode surface may cause the overpotential of zinc deposition to increase. In particular, when the content of the polymer additive increases to a certain extent, it will significantly increase the viscosity of the electrolyte, which may in turn weaken the fluidity of the liquid. Therefore, it is particularly important to accurately select the content of the polymer additive to prepare an electrolyte that promotes the homogeneous nucleation of zinc.

[0021] Compared with the prior art, the present application has the following beneficial effects:

[0022] The application provides a polymer additive capable of guiding homogeneous deposition of zinc ions, the polymer additive being sodium isobutenyl alcohol polyoxyethylene ether-acrylic acid-styrene sulfonic acid-hydroxyethyl acrylate copolymer, which is obtained by free radical copolymerization of isobutenyl alcohol polyoxyethylene ether, acrylic acid, sodium styrene sulfonic acid and hydroxyethyl acrylate. Meanwhile, the copolymer is used for preparing an aqueous zinc ion electrolyte, the obtained electrolyte can guide homogeneous deposition of zinc ions, obviously inhibit the occurrence of side reactions and the growth of dendrites, and the aqueous zinc ion electrolyte can effectively solve the short circuit and other problems caused by the growth of dendrites in the aqueous zinc ion battery, and can significantly improve the rate performance and cycle stability of the aqueous zinc ion battery. Therefore, the polymer additive provided by the application has great application potential in inhibiting side reactions and optimizing zinc deposition, and is helpful to develop an aqueous zinc ion battery with excellent performance and good energy storage application prospect. Overall, the application has the following advantages:

[0023] (1) The polymer additive provided by the application can be adsorbed on the surface of the zinc negative electrode, effectively adjust the local current density of the electrode tip, prevent the free diffusion of zinc on the surface of the negative electrode, and thus realize the homogeneous deposition of zinc. The adsorption layer not only can isolate active water molecules, but also can inhibit the occurrence of side reactions and the growth of dendrites, and thus improve the performance and stability of the battery.

[0024] (2) The preparation method of the polymer additive provided by the application is simple and easy to mass produce. Meanwhile, the raw materials used are cheap and easy to obtain, which reduces the production cost and improves the economic benefit.

[0025] (3) When the electrolyte containing the polymer additive provided by the application is applied to the aqueous zinc ion battery, it shows good reversibility, high safety and excellent electrochemical performance, so that the battery can exhibit better performance and longer service life in actual application. BRIEF DESCRIPTION OF DRAWINGS

[0026] Figure 1 SEM images of zinc foils soaked in electrolytes obtained in Examples 2-4 and Comparative Example 1.

[0027] Figure 2 SEM images of zinc foils deposited in electrolytes obtained in Example 3 and Comparative Example 1 at a current density of 5 mA·cm -2 for 30 min.

[0028] Figure 3 Time-current method test comparison chart of zinc foils soaked in electrolytes obtained in Examples 2-4 and Comparative Example 1.

[0029] Figure 4 Hydrogen evolution test comparison chart of zinc foils soaked in electrolytes obtained in Examples 2-4 and Comparative Example 1.

[0030] Figure 5 Zn||Cu asymmetric cells made with electrolytes of Examples 2-4 and Comparative Example 1 at 5 mA-cm -2 current density and 5 mA-h-cm -2 Coulombic efficiency plot at deposition capacity.

[0031] Figure 6 Zn||Cu asymmetric cells made with electrolytes of Example 3 and Comparative Example 1 at 10 mA-cm -2 current density and 1 mA-h-cm -2 Coulombic efficiency plot at deposition capacity.

[0032] Figure 7 Zn||Cu asymmetric cells made with electrolytes of Example 3 and Comparative Example 1 at 20 mA-cm -2 current density and 1 mA-h-cm -2 Coulombic efficiency plot at deposition capacity.

[0033] Figure 8 Zn||Zn symmetric cells made with electrolytes of Example 3 and Comparative Example 1 at 50 mA-cm -2 current density and 1 mA-h-cm -2 Cycle charge-discharge plot at deposition capacity.

[0034] Figure 9 Cycle charge-discharge plot at deposition capacity at 91% DOD for Zn||Zn symmetric cells made with electrolytes of Example 3 and Comparative Example 1.

[0035] Figure 10 Zn||NaVO full cells made with electrolytes of Example 3 and Comparative Example 1 at 4.17 A-g -1 Cycle life plot at current density.

[0036] Figure 11 Zn||NaVO full cells made with electrolytes of Example 3 and Comparative Example 1 at 0.3 A-g -1 Cycle life plot at current density. DETAILED DESCRIPTION

[0037] The specific embodiments of the present application will be further described with the following non-limiting examples. It is to be understood that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting. Furthermore, the use of the terms "first", "second", etc. are intended for illustrative purposes only and are not to be construed in a limiting sense.

[0038] The experimental methods in the following examples are all conventional methods unless otherwise specified. The experimental materials used in the following examples are all commercially available unless otherwise specified.

[0039] Example 1: A polymer additive and a preparation method thereof

[0040] The molecular structure of the polymer additive is shown below:

[0041]

[0042] The polymer additive is obtained by free radical copolymerization of sodium styrene sulfonate, acrylic acid, isobutylene alcohol polyoxyethylene ether and hydroxyethyl acrylate. The preparation method is as follows:

[0043] (1) 8 g of acrylic acid, 12 g of sodium styrene sulfonate (CAS No. 3039-83-6), 3 g of hydroxyethyl acrylate, 0.9 g of mercaptopropionic acid, 0.14 g of vitamin C and 75 g of water were dissolved to prepare a dropping solution;

[0044] (2) 50 g of water, 77 g of isobutylene alcohol polyoxyethylene ether (molecular weight 2400, CAS No. 31497-33-3) and 1.2 g of ammonium persulfate were added to a reaction bottle, stirred and dissolved, then heated to 35°C, then the dropping solution prepared in step (1) was slowly added, and the reaction temperature was controlled at 35-45°C for 2.5-3 h, then the reaction was continued for 2 h after the dropping was completed, and a polymer additive solution with a content of 45% was obtained. The number average molecular weight was 67020 measured by gel permeation chromatography (GPC). The GPC test conditions were: Waters 1515 GPC instrument, detector 2414 RI, mobile phase: pure water; room temperature test, standard sample: glucose.

[0045] Example 2: Preparation of aqueous zinc ion electrolyte based on polymer additive

[0046] The aqueous zinc ion battery electrolyte of this example contains 1M Zn(OTF)2+1.5% polymer additive of Example 1. The preparation method is as follows:

[0047] (1) 0.44 g of the polymer additive solution of Example 1 was weighed and diluted to 10 g with deionized water, and stirred for 5 min until the solution was mixed uniformly.

[0048] (2) 3.63 g of zinc trifluoromethanesulfonate was added to the clear solution obtained in step (1), and stirred for 10 min until the solution was mixed uniformly.

[0049] Example 3: Preparation of aqueous zinc ion electrolyte based on polymer additive

[0050] The aqueous zinc ion battery electrolyte of the present example contains 1M Zn(OTF)2+ 3.0% of the polymer additive of Example 1. The preparation method is as follows:

[0051] (1) 0.88 g of the polymer additive solution of Example 1 was weighed and diluted to 10 g with deionized water, and stirred for 5 min until the solution was uniformly mixed.

[0052] (2) 3.63 g of zinc trifluoromethanesulfonate was added to the clear solution of step (1), and stirred for 10 min until the solution was uniformly mixed.

[0053] Example 4: Preparation of aqueous zinc ion electrolyte based on polymer additive

[0054] The aqueous zinc ion battery electrolyte of the present example contains 1M Zn(OTF)2+ 4.5% of the polymer additive of Example 1. The preparation method is as follows:

[0055] (1) 1.32 g of the polymer additive solution of Example 1 was weighed and diluted to 10 g with deionized water, and stirred for 5 min until the solution was uniformly mixed.

[0056] (2) 3.63 g of zinc trifluoromethanesulfonate was added to the clear solution of step (1), and stirred for 10 min until the solution was uniformly mixed.

[0057] Comparative Example 1: Preparation of conventional aqueous zinc ion battery electrolyte

[0058] 3.63 g of zinc trifluoromethanesulfonate was added to 10 g of deionized water, and stirred to dissolve to obtain.

[0059] Experimental Example 1: Ion conductivity of different aqueous zinc ion battery electrolytes

[0060] The ion conductivities of the aqueous zinc ion battery electrolytes of Examples 2-4 and Comparative Example 1 were tested by a conductivity meter. As shown in Table 1, the polymer additive prepared in Example 1 can reduce the charge barrier on the electrode surface when used to prepare aqueous zinc ion battery electrolyte, thereby improving ion transmission efficiency.

[0061] Table 1 Ion conductivities of aqueous zinc ion battery electrolytes of Examples 2-4 and Comparative Example 1

[0062]

[0063] Experimental Example 2: Comparison of deposition of different aqueous zinc ion battery electrolytes on zinc foil surface

[0064] After the zinc foil was soaked in the aqueous zinc ion battery electrolytes of Examples 2-4 and Comparative Example 1 for 7 days, the SEM test results of the zinc foil surface were as follows: Figure 1As shown, it can be seen that the addition of the polymer additive of Example 1 can enable the electrolyte to be adsorbed on the surface of the zinc negative electrode and form a uniform solid electrolyte interface layer (SEI).

[0065] Meanwhile, the zinc foil was placed in the electrolyte of Example 3 and Comparative Example 1, respectively, and deposited for 30 min at a current density of 5 mA·cm-2, and the SEM test results of the surface of the zinc foil are shown in Figure 2 As shown, it can be seen that the SEI layer formed after the addition of the polymer additive of Example 1 in the electrolyte can induce more uniform deposition of Zn ions and inhibit the generation of dendrites.

[0066] Experimental Example 3: Comparison of dendrite growth of different aqueous zinc ion battery electrolytes

[0067] After the zinc foil was soaked in the aqueous zinc ion battery electrolytes of Examples 2-4 and Comparative Example 1 for 7 days, the test results of the chronoamperometry are shown in Figure 3 As shown, in the comparative example, the current density linearly increased within 300 s, indicating that the zinc deposition expanded with the growth of dendrites, while Examples 2-4 exhibited a stable current, indicating that the addition of the polymer additive of Example 1 in the electrolyte can limit the self-diffusion of Zn ions.

[0068] Experimental Example 4: Hydrogen evolution side reaction of different aqueous zinc ion battery electrolytes

[0069] After the zinc foil was soaked in the aqueous zinc ion battery electrolytes of Examples 2-4 and Comparative Example 1 for 7 days, linear sweep voltammetry (LSV) test was performed using an electrochemical workstation CHI 760E, with a mercury-mercury sulfate electrode as the reference electrode, a carbon rod as the counter electrode, and a 0.1 mm zinc sheet as the working electrode. The potential window for the LSV test was -1.6 V-1.0 V, and the scan rate was 5 mV / s.

[0070] The hydrogen evolution test results are shown in Figure 4 As can be seen, the hydrogen evolution potential window of the aqueous zinc ion battery electrolytes of Examples 2-4 is expanded compared to Comparative Example 1, indicating that the addition of the polymer additive of Example 1 can inhibit the decomposition of water.

[0071] Experimental Example 5: Battery performance test of different aqueous zinc ion battery electrolytes

[0072] The battery performance tests of the following examples were all performed using a new battery test system, and the assembled batteries included:

[0073] Zn||Zn symmetric battery: zinc foil was used as the positive and negative electrodes, a glass fiber membrane was used as the separator, and the electrolyte was the electrolyte prepared in Examples 2-4 or Comparative Example 1, and a 2025 button cell was assembled in an air atmosphere. Then the Zn||Zn symmetric battery was tested at different current densities (mA·cm-2) for 30 min, and the results are shown in As shown, the current density of the Zn||Zn symmetric battery of Example 2-4 is stable, indicating that the addition of the polymer additive of Example 1 in the electrolyte can limit the self-diffusion of Zn ions and inhibit the generation of dendrites.-2 ) and area capacity (mA h cm -2 ) to investigate whether the polymer additive of Example 1 can guide the uniform deposition of zinc ions on the surface of the negative zinc sheet.

[0074] Zn||Cu half-cell: A 2025 button cell was assembled in air atmosphere with zinc foil as the negative electrode, copper foil as the positive electrode, glass fiber membrane as the separator, and the electrolyte prepared in Example 2-4 or Comparative Example 1. Then the coulombic efficiency of the Zn||Cu half-cell under different current densities (mA cm -2 ) and area capacities (mA h cm -2 ) was tested to investigate the influence of the polymer additive of Example 1 on the deposition morphology of zinc ions.

[0075] Zn||NaVO cell: A 2025 button cell was assembled in air atmosphere with NaVO (NaV3O8·1.5H2O), acetylene black and PVDF mixed uniformly at a mass ratio of 80:10:10, then dissolved in NMP solution to form a slurry, and then uniformly coated on carbon paper to form a working electrode, with glass fiber as the separator, and the electrolyte obtained in Example 3 or Comparative Example 1, and then tested in the voltage range of 0.2V-1.6V vs Zn / Zn 2+ .

[0076] Figure 5 is the coulombic efficiency plot of Zn||Cu asymmetric cells made with the electrolytes of Example 2-4 and Comparative Example 1 under a current density of 5 mA cm -2 and a deposition capacity of 5 mA h cm -2 . It can be seen that when the electrolyte contains the polymer additive of Example 1, the Zn||Cu cell shows more excellent stability and higher average coulombic efficiency during cycling. Among them, Comparative Example 1, Example 2 and Example 4 failed at the 10th, 140th and 250th cycles, respectively, while the electrolyte of Example 3 can be stably cycled for 340 times at a high current and high capacity with a high average coulombic efficiency of 98.3%.

[0077] Figure 6 is the coulombic efficiency plot of Zn||Cu asymmetric cells made with the electrolytes of Example 3 and Comparative Example 1 under a current density of 10 mA cm -2 and a deposition capacity of 1 mA h cm -2Coulombic efficiency plot under deposition capacity. From which it can be seen that when the electrolyte contains the polymer additive of Example 1, the Zn||Cu battery shows more excellent stability and higher average coulombic efficiency when cycled. Among them, the electrolyte obtained by Example 3 can be stably cycled for 1630 times at a high average coulombic efficiency of 98.5%, while Comparative Example 1 fails at 49 cycles.

[0078] Figure 7 Zn||Cu asymmetric battery made with the electrolyte of Example 3 and Comparative Example 1 at a current density of 20 mA·cm -2 Current density and 1 mA·h·cm -2 Coulombic efficiency plot under deposition capacity. From which it can be seen that when the electrolyte contains the polymer additive of Example 1, the Zn||Cu battery shows more excellent stability and higher average coulombic efficiency when cycled. Among them, the electrolyte obtained by Example 3 can be stably cycled for 1630 times at a high average coulombic efficiency of 98.5%, while Comparative Example 1 fails at 49 cycles.

[0079] Figure 8 Zn||Zn symmetric battery made with the electrolyte of Example 3 and Comparative Example 1 at a current density of 50 mA·cm -2 Current density and 1 mA·h·cm -2 Cycle charge-discharge curve plot under deposition capacity. From which it can be seen that when the electrolyte contains the polymer additive of Example 1, the Zn||Zn symmetric battery shows more excellent stability when cycled, and has a great improvement in life. Among them, the battery assembled by the electrolyte obtained by Example 3 can be stably worked for more than 400h at 91% DOD under the extreme condition of super-high zinc utilization rate, while the corresponding symmetric battery of Comparative Example 1 fails after 20h. -2 Current density and 1 mA·h·cm -2 Can be stably worked for more than 140h respectively under deposition capacity.

[0080] Figure 9 Cycle charge-discharge curve plot of Zn||Zn symmetric battery made with the electrolyte of Example 3 and Comparative Example 1 at a deposition capacity of 91% DOD. From which it can be seen that when the electrolyte contains the polymer additive of Example 1, the Zn||Zn symmetric battery shows more excellent stability when cycled, and has a great improvement in life. Among them, the battery assembled by the electrolyte obtained by Example 3 can be stably worked for more than 400h at 91% DOD under the extreme condition of super-high zinc utilization rate, while the corresponding symmetric battery of Comparative Example 1 fails after 20h.

[0081] Figure 10 Zn||NaVO full battery made with the electrolyte of Example 3 and Comparative Example 1 at a current density of 4.17 A·g -1Cycle life curves of Zn||NaVO full cells at a current density of 4.17 A·g -1 -1. From the curves, it can be seen that when the electrolyte contains the polymer additive of Example 1, the Zn||NaVO full cell can have a specific capacity of more than 130 mAh·g -1 -1 after 5000 cycles at a current density of 4.17 A·g

[0082] Figure 11 Cycle life curves of Zn||NaVO full cells at a current density of 0.3 A·g -1 -1. From the curves, it can be seen that when the electrolyte contains the polymer additive of Example 1, the Zn||NaVO full cell can have a specific capacity of more than 200 mA·h·g -1 -1 after more than 600 cycles at a current density of 0.3 A·g -1 -1. From the curves, it can be seen that when the electrolyte contains the polymer additive of Example 1, the Zn||NaVO full cell can have a specific capacity of more than 200 mA·h·g

[0083] In summary, the polymer additive provided by the present application has the characteristics of simple synthesis, low price, green environmental protection and large-scale production. At the same time, the polymer additive can be preferentially adsorbed on the surface of zinc metal to form a uniform protective layer, thereby guiding the homogeneous deposition of zinc ions and significantly inhibiting the occurrence of side reactions and the growth of dendrites. In addition, the aqueous zinc ion battery electrolyte prepared by using the polymer additive can effectively solve the short circuit problem caused by the growth of dendrites in the aqueous zinc ion battery, and can significantly improve the rate performance and cycle stability of the aqueous zinc ion battery. Therefore, the polymer additive provided by the present application has great application potential in inhibiting side reactions and optimizing zinc deposition, and is helpful to develop an aqueous zinc ion battery with excellent performance and good energy storage application prospect.

[0084] The embodiments of the present application are described in detail above, but the present application is not limited to the described embodiments. For those skilled in the art, various changes, modifications, replacements and variations of the embodiments can be made without departing from the principles and spirits of the present application, and still fall within the protection scope of the present application.

Claims

1. A polymer as an electrolyte additive in a zinc ion battery, characterized in that: The polymer is a copolymer of isobutylene alcohol polyoxyethylene ether, acrylic acid, sodium styrene sulfonate and hydroxyethyl acrylate, the number average molecular weight of the polymer is 30,000-80,000, and the molecular structure of the polymer is shown in Formula I: 。 2. The use according to claim 1, characterized in that The polymer is obtained by free radical copolymerization of isobutylene alcohol polyoxyethylene ether, acrylic acid, sodium styrene sulfonate and hydroxyethyl acrylate, and specifically comprises the following steps: S1. Dissolve acrylic acid, sodium styrene sulfonate, hydroxyethyl acrylate, mercaptopropionic acid and vitamin C in water to prepare a dropping solution; S2. Dissolve isobutylene alcohol polyoxyethylene ether and ammonium persulfate in water, heat to 30-35°C, then dropwise add the dropping liquid of step S1, and control the dropping to be completed within 2.5-3 hours. During this period, control the reaction temperature to be 35-45°C. After the dropping is completed, continue the reaction for 2-3 hours. After the reaction is completed, the product is obtained.

3. The use according to claim 2, characterized in that The mass ratio of the isobutylene alcohol polyoxyethylene ether, acrylic acid, sodium styrene sulfonate, hydroxyethyl acrylate, ammonium persulfate, vitamin C and mercaptopropionic acid is 65-80: 5-10: 5-15: 2.5-10: 1-1.5: 0.1-0.15: 0.5-1.

0.

4. The use according to claim 2, characterized in that The molecular weight of the isobutylene alcohol polyoxyethylene ether is 1200-2400.

5. The use according to claim 1, characterized in that The zinc ion battery is an aqueous zinc ion battery.

6. An aqueous zinc ion battery electrolyte, characterized in that The electrolyte comprises the polymer according to claim 1, a zinc salt and water.

7. An aqueous zinc ion battery electrolyte according to claim 6, characterized in that: The zinc salt is selected from at least one of zinc sulfate, zinc trifluoromethanesulfonate and zinc perchlorate.

8. An aqueous zinc ion battery electrolyte according to claim 6, characterized in that: The concentration of the zinc salt is 0.5-3M.

9. An aqueous zinc ion battery electrolyte according to claim 6, characterized in that: The mass concentration of the polymer in the electrolyte is 1.5%-4.5%.

Citation Information

Patent Citations

  • Electrolyte containing anionic polymer, zinc ion battery and preparation method and application of zinc ion battery

    CN115084674A

  • High-strength concrete viscosity reduction type polycarboxylate superplasticizer and preparation method thereof

    CN116693769A